Government Policies Supporting Digital Economic Trans-formation for Sustainable MSME Development in Indonesia - Muhammad Fiki Febriyan (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Digital economic transformation has become one of the key strategies for promoting national economic growth through the integration of digital technologies across various sectors, including Micro, Small, and Medium Enterprises (MSMEs). MSMEs play a strategic role in Indonesia's economy by contributing to employment creation, income generation, and Gross Domestic Product (GDP) growth. However, the digitalization of MSMEs continues to face several challenges, including limited digital literacy, inadequate technological infrastructure, and the underutilization of digital services by business actors. This study aims to analyze the role of government policies in supporting digital economic transformation to foster the sustainable development of MSMEs in Indonesia. A qualitative approach employing a literature review method was adopted by examining scholarly journal articles, academic books, government documents, and reports published by international organizations. The findings indicate that government initiatives, in-cluding Making Indonesia 4.0, the Quick Response Code Indonesian Standard (QRIS), the Online Single Submission (OSS) system, and the National Movement for Proudly Made in Indonesia (Gernas BBI), have positively contributed to improving operational efficiency, expanding market access, strengthening fi-nancial inclusion, and enhancing the competitiveness of MSMEs. Nevertheless, the effectiveness of these policies is influenced by the readiness of human resources, the availability of digital infrastructure, and collaboration among relevant stakeholders. Therefore, continuous strengthening of digital transformation policies is essential to establish an inclusive digital ecosystem, improve the competitiveness of MSMEs, and support sustainable economic development in Indonesia.